Designer of "PESMART" App Website for Cooperatives in the UHAMKA Dormitory Environment - Rivaldi, Muhamad Sadam; Hanif, Isa Faqihuddin; Farhan Nurhidayah; Pajar Marpandi; Fauzan, Nabil Ahmad (Journal of Advances in Information and Industrial Technology, 2024)
Financial management and an efficient cashier system are critical elements in an institution's operations, including student dormitories. This research aims to design and develop the "PESMART" mobile application aimed at cooperative cashier management in the UHAMKA Dormitory. This application is designed to make it easier to manage financial transactions, monitor inventory, and provide real-time financial reports. The methodology used in developing this application is an Agile approach, which allows fast iteration and response to user feedback. Data was collected through interviews and surveys with hostel staff to identify critical needs. A wireframe design and interactive prototype were created using Figma. Initial test results show that the "PESMART" application has succeeded in increasing cashier management efficiency and reducing transaction recording errors. User satisfaction surveys indicate high satisfaction with the ease of use and features provided by the application. In conclusion, "PESMART" provides an effective digital solution for financial and cashier management in a dormitory environment, with recommendations for developing additional features in the future to further improve functionality and user experience.